PENERAPAN KEPEMIMPINAN TRANSFORMASIONAL UNTUK MENINGKATKAN KREATIVITAS DOSEN: PENERAPAN KEPEMIMPINAN TRANSFORMASIONAL UNTUK MENINGKATKAN KREATIVITAS DOSEN - Roy Setiawan; Dedy Triyono (LPPM Universitas Islam Darul 'Ulum Lamongan, 2022)
This service activity is carried out with the aim of socializing the role of transformational leadership on the performance of lecturers. in universities in Indonesia. The implication of this research is that higher education leaders must pay attention to lecturers to improve creative performance. This can be achieved by paying attention to the Intellectual Stimulation aspect.